Improving screening, brief intervention and referral to treatment for unhealthy alcohol use in diverse, low-resourced primary care clinics - Melinda M. Davis; Jennifer Coury; Victoria Sanchez; Erin S. Kenzie; Jean Hiebert Larson; Chrystal Barnes; James L. McCormack; Robert Durr; Tiffany Weekley; Alissa Robbins; Maya Singh; Brigit A. Hatch (BMC, 2024)
Abstract Background Implementation of screening brief intervention and referral to treatment (SBIRT) and medication-assisted treatment for alcohol use disorder (MAUD) remains low in primary care. ANTECEDENT (Partnerships to Enhance Alcohol Screening, Treatment, and Intervention) was a practice-facilitator led implementation study to increase SBIRT and MAUD use in diverse primary care clinics. Methods From November 2019 - April 2023, we conducted a convergent parallel mixed methods evaluation. Participants were small and medium-sized primary care clinics in the Northwestern U.S. Clinics received foundational support (i.e., baseline/exit assessment, access to SBIRT Oregon website) and the option for supplemental implementation support (e.g., practice facilitation, expert consultation) over the 15-month intervention to improve SBIRT and MAUD. Qualitative and quantitative data regarding clinic characteristics, implementation strategies, and SBIRT/MAUD outcomes were collected through practice facilitator interviews, periodic reflections and clinic contact logs, interviews, pre-post surveys, and electronic health record (EHR) queries. Quantitative analyses included descriptive statistics, logistic regression, and the Wilcoxon sign-ranked test. Qualitative analysis took an immersion crystallization approach. Data were reviewed in a matrix to evaluate intervention adoption, implementation, and effectiveness. Results We recruited 75 unique clinics; 66 participated and 48 (73%) completed the study. Eight participating clinics chose to receive foundational support only (12%) while 58 chose to engage in supplemental support (88%) activities. Clinics that received supplemental support and completed the intervention (n = 42) engaged in practice facilitation (Mean: 293 min, range: 75-550 min); data review (38%), HIT support (31%), expert consultation (19%), and peer-to-peer learning (5%). Pre- and post-intervention assessments showed significant improvement in self-reported SBIRT process outcomes. Performance data improved among the subset of completing clinics able to produce data (n = 17). Clinics described positive experiences with ANTECEDENT support and highlighted remaining barriers to SBIRT and MAUD implementation. Conclusions Participating clinics engaged in a diverse range of supportive activities. A flexible approach using practice facilitation and implementation support could be helpful for low-resourced primary care clinics in improving SBIRT and MAUD for unhealthy alcohol use.